Decentralization and its discontents an essay on class, political agency and national perspective in Indonesian politics - Lane, Max 1951- (ISEAS Publishing, 2014)
"This book opens up the discussion on the history and political economy of the new populist policies that seem to gain momentum in the face of the Indonesian elections. It also addresses questions pertaining to the problems and options related to popular aspirations within this context." - Professor Olle Toernquist, University of Oslo